Revelation, Intellectual Intuition and Reason in the Philosophy of Mulla Sadra : an Analysis of the al-hikmah al-'arshiyyah. - Moris, Zailan (Routledge Sufi series., 2013)
This book examines and analyses the legitimacy of the widely held claim that Mulla Sadra's philosophy (al-hikmah al-muta'aliyyah) is a synthesis of principles and doctrines drawn from revelation (wahy), gnosis ('irfan/ma'rifah) and discursive philosophy (al-hikmah al-bahthiyyah). In Mulla Sadra's view, these three major sources of knowledge can be brought together without contradiction and accorded their respective roles in the human quest for true and certain knowledge. This book discusses and demonstrates how Mulla Sadra achieves this synthesis as.